Combination of FDM 3D Printing and Compressed Tablet for Preparation of Baclofen as Gastro-Floating Drug Delivery System (Conference Paper )# - Abdulkhaleq, Nuha Mohammed; Ghareeb, Mowafaq M. (Iraqi Journal of Pharmaceutical Sciences, 2023)
This study aimed to develop an oral drug delivery system for gastro-retentive sustained drug release of baclofen by using a 3D printed capsular device since baclofen has a short half-life of 2.5 to 4 hours and has a narrow absorption window. Firstly sustained-release tablets of baclofen were formulated through the hot-melt extrusion of various thermoplastic polymers and direct compression of the extrudate, then a capsular device was designed and 3D printed to contain two air pockets to enable floating of the device and has four windows for drug release. 3D printing of the capsular device was done by an FDM printer using biodegradable PLA filament, and the sustained release tablets were inserted into the device to allow the medicine to be released into the stomach over a longer period. An in vitro buoyance test and an in vitro dissolution test were used to examine the buoyancy and sustained-release features of the formulated gastro-floating system. Five sustained release formulas were developed using different thermoplastic polymers in hot-melt extrusion. Produced tablets were assayed for drug content, hardness, and friability while a DSC study was done on the selected formula. F 5 which contains 20% baclofen, 55% Eudragit RS-100, 20% ethylcellulose, and 5% PEG 4000 showed sustained release where the complete dissolution of the drug occurred in 12 hours, and the gastro-floating device remained floating all the time. This method has a great potential for developing various floating drug delivery systems with the required release profile.